The Effect of High Hydrostatic Pressure (HHP) Induction Parameters on the Formation and Properties of Inulin–Soy Protein Hydrogels - Anna Florowska; Tomasz Florowski; Patrycja Goździk; Adonis Hilal; Hanna Florowska; Emilia Janiszewska-Turak (Gels)
The aim of this study was to determine the effect of high hydrostatic pressure (HHP) induction parameters on the formation and properties of inulin–soy protein hydrogels. Solutions containing 20 g/100 g of inulin and 3 or 6 g/100 g of soy protein isolate (3 SPI; 6 SPI) were subjected to HHPs of 150, 300, or 500 MPa for 5, 10, or 20 min. The HHP parameters had no significant impact on the effectiveness of hydrogel formation. In most cases, the time of solution pressurization had no significant effect on the characteristics of hydrogels. However, increasing the induction pressure from 150 to 300 MPa resulted in hydrogels with different characteristics being obtained, e.g., more flattened microstructure; higher stability (only 3 SPI); higher yield stress, firmness, and adhesiveness; and lower spreadability. These changes were more noticeable in the hydrogels with lower protein content. An increase in the induction pressure (to 500 MPa) did not result in a significant strengthening of the hydrogel structure. However, in the case of 6 SPI hydrogels, induction with a pressure of 500 MPa had an unfavorable effect on their stability. The results indicate that HHP (300 MPa) can be used as an effective method for strengthening the structure of inulin–protein hydrogels.